2015
DOI: 10.1016/j.gca.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in magnetite from massive iron oxide-apatite deposits indicate a combined formation by igneous and magmatic-hydrothermal processes

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. data demonstrate that a saline magmatic-hydrother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(127 citation statements)
references
References 72 publications
12
104
0
Order By: Relevance
“…10. Cr vs. V plot discriminating Kiruna-type from other ore deposit proposed by Knipping et al (2015). Many of the magnetite grains from the Kiruna and El Laco magnetite-apatite ores in this study contain higher Cr concentrations than suggested in this diagram.…”
Section: Trace Element Chemistry Of the El Laco Magnetitesupporting
confidence: 44%
See 2 more Smart Citations
“…10. Cr vs. V plot discriminating Kiruna-type from other ore deposit proposed by Knipping et al (2015). Many of the magnetite grains from the Kiruna and El Laco magnetite-apatite ores in this study contain higher Cr concentrations than suggested in this diagram.…”
Section: Trace Element Chemistry Of the El Laco Magnetitesupporting
confidence: 44%
“…In a broad sense, there are two genetic models to describe how magnetite-apatite deposits formed in favor today, with a third model that involves a combination of the first two models: 1) Originating from immiscible iron-rich melts that separated from a silicate melt and were emplaced at subvolcanic levels or erupted and cooled at the surface (e.g., Henríquez and Martin, 1978;Nyström and Henríquez, 1994;Naslund et al, 2002;Nyström et al, 2008;Martinsson, 2016); 2) Metasomatic replacement of the host rocks by hydrothermal fluids (e.g., Hitzman et al, 1992;Rhodes and Oreskes, 1999;Sillitoe and Burrows, 2002;Edfelt et al, 2005;Groves et al, 2010;Valley et al, 2011;Dare et al, 2015;Westhues et al, in press); and 3) a magmatic-hydrothermal combination of these two models (e.g., Knipping et al, 2015;Tornos et al, 2016). A sedimentaryexhalative origin was suggested by Parák (1975) but was not widely accepted (Frietsch, 1978;Nyström et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of apatite, as documented for Chadormalu, appears to be a common feature in IOA type ore deposits (e.g., Kiirunavaara magnetite-apatite ore [53], Los Colorados iron oxide-apatite [83], and Se-Chahun magnetite-apatite deposit [36]). Such reequilibration and modification in Chadormalu ore was already documented for magnetite by Heidarian et al [21].…”
Section: Timing Of Apatite Alteration and Its Implicationmentioning
confidence: 72%
“…The authors propose a model involving sedimentary carbonates and subsequent metasomatism by REE-rich hydrothermal fluids. Magnetite chemistry has proven critical for understanding the transition from magmatic to hydrothermal conditions in Kiruna-type iron oxide-apatite (IOA) deposits [119].…”
Section: Iron-oxide-apatite (Ioa) and Iron-oxide Copper Gold (Iocg) Dmentioning
confidence: 99%